Immigrants in Poland – the culture of reception - NECEL, WOJCIECH (Prawo Kanoniczne, 2017)
The migration of population in the second decade of the twenty-rst century, in the lives of the global, as well as inter-continental and inter- national communities, is a structural phenomenon undergoing intensi- cation and it is aecting all areas of human life and the life of the Church. e Church in Poland got used to speaking about Polish emigration, the “very old” one and the “old” one, as well as the latest, which came about alongside joining the structures of the European Union and the Schengen group. A vital problem within the immigration area is the return of Polish families to Poland, at least from the British Isles and France, and, gaining dynamics from time to time, the issue of repatriation of Poles from distant Kazakhstan and the presence of Ukrainians and other Eastern nationalities on the streets of Polish cities. Mass media inform about the situation on Lampedusa island, on the Syrian-Turkish and Turkish-Iraqi borders, and the situation in the Balkans and Hungary. e crisis plunged Greece cannot manage to solve the prob- lems of the coming people. Pope Francis sympathized with the European immigrants, lamented that so many of them deceased on the way to the European continent. e politicians discussed how to divide the coming groups of refugees among the countries. With the foregoing outline, at the turn of 2014-2015, the Republic of Poland along with the rest of European Union, is faced with the necessity to develop a common immigration policy, and the Church, in agreement with the Erga migrantes instruction, should elaborate the specics of the ministry towards the immigrants.